PEMBELAJARAN PRA-MATEMATIKA MELALUI BAHASA VERBAL UNTUK ANAK USIA DINI SELAMA BELAJAR DARI RUMAH - I Komang Sesara Ariyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The Covid-19 pandemic has an impact on the education sector, especially in the field of early childhood education in Indonesia. Some educational institutions have been facilitated with an online learning system, but others still have to do face-to-face learning with small study group sizes. Apart from educators in early childhood education, the role of parents is the key to the success of early childhood education during this pandemic. Early childhood has the characteristics of pre-concrete thinking, where concrete media is needed to be able to encourage children to pronounce the vocabulary, thus making it easier for young children to learn pre- math. The concrete media can be objects that are in the house or objects that exist in nature. As child get older, his/her vocabulary becomes richer, and a rich vocabulary will help children understand pre-math concepts. This paper discusses pre-math learning through verbal language for early childhood during learning from home, starting from how language is for early childhood, what verbal language is in pre-math learning, and how pre-math learning for early childhood while studying at home through verbal language.